Respiratory droplet generation and dispersal during nasoendoscopy and upper respiratory swab testing. Issue 10 (4th July 2020) - Tan, Vanessa Y. J.; Zhang, Edward Z. Y.; Daniel, Dan; Sadovoy, Anton; Teo, Neville W. Y.; Kiong, Kimberley L.; Toh, S. T.; Yuen, Heng‐Wai
Abstract: Respiratory particle generation and dispersal during nasoendoscopy and swab testing is studied with high‐speed video and laser light illumination. Video analysis reveals droplet formation in three manoeuvres during nasoendoscopy ‐ sneezing, vocalization, and nasal decongestion spray. A capillary bridge of mucus can be seen when a nasoendoscope exits wet nares. No droplet formation is seen during oral and nasopharyngeal swab testing. We outline the following recommendations: pull the face mask down partially and keep the mouth covered, only allowing nasal access during nasoendoscopy; avoid nasal sprays if possible; if nasal sprays are used, procedurists should be in full personal protective equipment prior to using the spray; withdrawal of swabs and scopes should be performed in a slow and controlled fashion to reduce potential dispersion of droplets when the capillary bridge of mucus breaks up.